Duplication Xp11.22-p14 in females: does X-inactivation help in assessing their significance? - Evers, Christina; Mitter, Diana; Strobl‐Wildemann, Gertrud; Haug, Ulrich; Hackmann, Karl; Maas, Bianca; Janssen, Johannes W. G.; Jauch, Anna; Hinderhofer, Katrin; Moog, Ute (American journal of medical genetics, 2015)
In females, large duplications in Xp often lead to preferential inactivation of the aberrant X chromosome and a normal phenotype. Recently, a recurrent ∼4.5 Mb microduplication of Xp11.22-p11.23 was found in females with developmental delay/intellectual disability and other neurodevelopmental disorders (speech development disorder, epilepsy or EEG anomalies, autism spectrum disorder, or behavioral disorder). Unexpectedly, most of them showed preferential inactivation of the normal X chromosome. We describe five female patients carrying de novo Xp duplications encompassing p11.23. Patient 1 carried the recurrent microduplication Xp11.22-p11.23, her phenotype and X-chromosome inactivation (XI) pattern was consistent with previous reports. The other four patients had novel Xp duplications. Two were monozygotic twins with a similar phenotype to Patient 1 and unfavorable XI skewing carrying an overlapping ∼5 Mb duplication of Xp11.23-p11.3. Patient 4 showed a duplication of ∼5.5 Mb comparable to the twins but had a more severe phenotype and unskewed XI. Patient 5 had a ∼8.5 Mb duplication Xp11.23-p11.4 and presented with mild ID, epilepsy, behavioral problems, and inconsistent results of XI analysis. A comparison of phenotype, size and location of the duplications and XI patterns in Patients 1-5 and previously reported females with overlapping duplications provides further evidence that microduplications encompassing Xp11.23 are associated with ID and other neurodevelopmental disorders in females. To further assess the implication of XI for female carriers, we recommend systematic analysis of XI pattern in any female with X imbalances that are known or suspected to be pathogenic. © 2015 Wiley Periodicals, Inc.